2018
DOI: 10.3390/mti2030060
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on Authenticity in Chat Bots

Abstract: In 1950, Alan Turing proposed his concept of universal machines, emphasizing their abilities to learn, think, and behave in a human-like manner. Today, the existence of intelligent agents imitating human characteristics is more relevant than ever. They have expanded to numerous aspects of daily life. Yet, while they are often seen as work simplifiers, their interactions usually lack social competence. In particular, they miss what one may call authenticity. In the study presented in this paper, we explore how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…One aspect of UX in the context of AI is how human-like chatbots should behave, and how this a ects UX. Although previous studies have explored how chatbots could evolve to converse or behave in a human-like manner [2,21,27,30,33,56], there is no consensus on whether this is the correct way to move forward from a UX perspective of interacting with chatbots [37,43,48].…”
Section: Designing a Chatbot With Humannessmentioning
confidence: 99%
See 3 more Smart Citations
“…One aspect of UX in the context of AI is how human-like chatbots should behave, and how this a ects UX. Although previous studies have explored how chatbots could evolve to converse or behave in a human-like manner [2,21,27,30,33,56], there is no consensus on whether this is the correct way to move forward from a UX perspective of interacting with chatbots [37,43,48].…”
Section: Designing a Chatbot With Humannessmentioning
confidence: 99%
“…However, studies have shown that users are attracted to human-like chatbots [2] and AI that allows for a human-like use of language [21]. Whether a chatbot should imitate human behavior or have their own personality could be dependent on context [37].…”
Section: Designing a Chatbot With Humannessmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with this constant introduction of new chatbots and new supporting services, the field is losing sight on what is necessary to build a chatbot that the user interacts with as if it has a mind of its own: The ultimate goal when it comes to social bots. Neurerer and colleagues [5] state that making a conversational agent acceptable to users is primarily a social, not only a technical, problem to solve. Therefore, a chatbot should not only have the capability of understanding what the user wants, but have the social characteristics to converse with the user as if it were completely autonomous.…”
Section: Introductionmentioning
confidence: 99%